Ivermectin in Human Medicine, An Overview of the Current Status of Its Clinical Applications - Gonzalez, P.; A. Gonzalez, F.; Ueno, K. (Current Pharmaceutical Biotechnology, 2012)
Ivermectin is a broad spectrum antiparasitic veterinary drug introduced in human medicine in 1987. It is considered the drug of choice in onchocerciasis and strongyloidiasis infections, and remains as a therapeutic option for mass treatment in lymphatic filariasis, for which it has widely proved its efficacy. While research continued for human use, new therapeutic targets for ivermectin have emerged. It is currently the better therapeutic option in the treatment of gnathostomiasis and crusted scabies, and could be an alternative option in ascariasis and Mansonella infections. Although these uses are already included in clinical guidelines, more trials are needed to increase their grade of evidence and to obtain their official approval. Concerning other minor uses such as the treatment of enterobiasis or against Trichuris trichiura, more research is still needed in order to test the real activity of ivermectin. The use of ivermectin in human medicine has shown an outstanding low rate of adverse reactions, with the exception of treatment of loiasis and onchocerciasis, where the death of a high microfilarial load may cause severe encephalopathy. However special attention must be paid to the emergence of the first documented cases of resistance in treatment of scabies.
Keywords: ivermectin